Experimental Study of Isopropyl Acetate and Acetone Additive Gasoline on a Spark-Ignition Engine and its Impact on Green Environment - Anbazhaghan, N.; Neupane, Gaurab; Lakshmanan, T.; Jayaprabakar, J.; Parthipan, J. (Recent Patents on Mechanical Engineering, 2025)
BackgroundGasoline engines using alcohol fuels are being researched in the present trend since they are seen to be viable as diesel engines. The effect of isopropyl acetate and acetone additive blends on gasoline is explored in this study using a single-cylinder four-stroke gasoline engine operating at a constant speed of 2500 rpm under all loading conditions.MethodsTwo gasoline blends are prepared by adding 5% and 10% by volume of isopropyl acetate and acetone separately. Properties are investigated and tested for its engine performance and emission.ResultsThe trial results demonstrated that the A5 (5% Acetone + 95% Gasoline) brake thermal efficiency improved when compared to pure gasoline. At maximum engine load, all additive blends have lower brake specific fuel consumption than pure gasoline. However, under full load, the emissions of various additive blends are lower than those of pure gasoline.ConclusionResults revealed that IA5 (5% Isopropyl acetate + 95% Gasoline), IA10 (10% Isopropyl acetate + 90% Gasoline), and A10 (10% Acetone + 90% Gasoline) are considered good for decreasing HC, NOx, and CO emissions respectively. The findings of this study can be considered as a patent to lay the information on these types of alcohols in gasoline engines.
Keywords: Gasoline